Desain Lanskap Pekarangan Terpadu di Pekon Negeri Ratu, Pesisir Barat - Indah Prastiwi (http://arl-faperta.ipb.ac.id/, 2020)
Community empowerment in optimizing integrated housing is aimed at making the community to be able to utilize the houses in order to improve the quality of the environment and people's lives. In addition, community empowerment must be able to run sustainably so as to provide sustainable benefits for the community. Proper yard management in this case is an integrated yard by combining various yard management technologies. In the community empowerment program, it adopts technology from an integrated farming system that are utilizing fish, plants and livestock. The series of activities in the community empowerment program for the yard utilization include providing various training in managing the yard and supporting technology. The provided training including composting from livestock manure and inorganic waste, introduction of biopore, and planning an integrated yard making. The series of activities carried out within a period of 2 months. Training is given so that the community can be independent in making integrated yards, so that this program can provide benefits on an ongoing basis. In this empowerment program, training is carried out and making sample yards using an integrated system. Integrated yard management design includes chicken coops or cattle, fish ponds, and vegetable or medicinal plants. The three components are designed to provide integrated benefits. The main design is a cattle pen placed above the fish pond, and plants placed around the pond. In general, the system is built so that manure will be disposed into the fish ponds to become feed. Then the water from the fish pond can be recirculate to irrigate the plants. Keywords: Aquaponic, Integrated Yard, Landscape Management, Pekarangan